The effect of global e-commerce on taxation legislation and the permanent establishment concept in South Africa - Young, Nikita Jade (Rhodes University, Faculty of Commerce, Department of Accounting, 2013)
The objective of this thesis was to analyse the effect of the increasing popularity of global e-commerce on the South African legislative framework in respect of the taxation of non-resident enterprises, and to propose a possible solution for the taxation of e-commerce, taking into account previous theories. The methodology utilised comprised of a critical analysis of the legal rules relating to the taxation of a foreign entity's business profits by virtue of the application of the permanent establishment principle, its definition and evolution as a conceptual basis for taxation. Furthermore, an in depth evaluation of the various solutions that have already been proposed and, in some cases, implemented was undertaken. It was concluded that the application of the permanent establishment principle is wholly ineffective as a means to levy tax on the e-commerce business profits of a foreign entity as the principle relies too heavily upon a physical intermediary in the source state, whereas e-commerce transactions are conducted on the intangible trading platform of the Internet. In light of the numerous policy proposals advanced over the years, it was concluded that the most feasible and practical solution for the taxation of foreign e-commerce would be the imposition on a foreign entity in South Africa of a low withholding tax on the active business profits in excess of a pre-determined threshold. Key words: South African taxation; e-commerce; foreign business entity; permanent establishment; withholding tax
Keywords: Electronic commerce; Electronic commerce -- Taxation; Electronic commerce -- South Africa; Taxation -- Law and legislation -- South Africa; South African taxation; E-commerce; Permanent establishment; Foreign business entity